LANGUAGE STYLE IN FACEBOOK STATUS - Alfina Gustiany Siregar (UIN Sumatera Utara, 2019)
This study addresses language style, different ways of communicating, and the purposes of communication of male and female in Facebook status. The objectives of the study are: a) to find out the dominant type of language style used by male and female; b) to describe the way of communicating between male and female; and c) to describe the purposes of communication of male and female in Facebook status. The data were obtained from 33 males’ statuses and 33 females’ statuses in March 2019. The data were analyzed based on two theories, first is three types of language style according to Joos (1967), they are formal style, consultative style and casual style. Second is the purposes of Facebook communication according to Patrick (2010), they are entertainment, integration into community, relationship maintenance, and identity construction. The findings show that: a) the dominant style used by both male and female in Facebook status are consultative style; b) The reasons of communication of male and female in Facebook status are: identity construction, giving information, praying, feeling, and giving advice.